Peningkatan Pemasaran Dengan Cara Pendekatan Konsumen Terhadap Penggunaan Jasa J&T Ekspress - Rifky Budi Setiawan (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This research was conducted in Mongonsidi Medan where this study aims to determine how the influence of the service marketing mix consisting of: Product (X1), Promotion (X2), on the consumer's purchase decision (Y) to use the J&T expedition service of the Mongonsidi Branch in Medan. The population in this study was 375 consumers with a sample size of 79 samples. The sample size is determined by the Slovin formula with an error tolerance of 10%. The study was conducted from June to October 2019. Sources of data used primary data taken directly from respondents. The results showed that product, promotion, price, location, people, physical evidence, and process had a positive and significant effect either partially or simultaneously on purchasing decisions to use J&T expedition services in the Mongonsidi Branch of Medan. Process variables were the variables that most influenced consumer purchasing decisions. . Products, promotions, prices, locations, people and physical evidence, and processes contributed 88.0% to the formation of consumer purchasing decisions. Products, promotions, prices, locations, people and physical evidence, and processes have a very strong relationship to consumer purchasing decisions.